PENGARUH DEWAN DIREKSI, DEWAN KOMISARIS DAN KOMITE AUDIT TERHADAP KINERJA KEUANGAN (STUDI EMPIRIS PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2021) - Rosdiana Rosdiana (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2023)
This study aims to investigate the effects of of the Board of Directors, Board of Commissioners and Audit Committee on the Financial Performance of Banking Companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. The research sample consists of 28 commercial banks by selecting each company with financial statements that include the number of the Board of Directors, Board of Commissioners and Audit Committee. The results of the study show that the Board of Directors has a significant negative effect on financial performance. While the Board of Commissioners and the Audit Committee have no effect on financial performance.